MULTILINGUAL INTERACTION IN CLASSROOM CONTEXT - Andi Muhammad Syafri Idris; Adliah Adliah; Syatria Alfina (Universitas Islam Negeri Alauddin Makassar, 2020)
This research aimed at exploring teacher and student ways of interacting in multilingual EFL classrooms. This research was a qualitative study using case study design. This research participants consisted of 1 EFL and 4 SMKN 5 Jeneponto students at Sulawesi Selatan. The data was obtained by observation and interview. The data was analyzed on the basis of data analysis procedure consisting of data collection, data display, data condensation, and conclusion: drawing / verification. The finding showed that there were three ways through multilingual interaction in the teaching and learning process, beginning the class, during learning process and closing the class. The findings led to the conclusion that the multilingual interaction within the classroom had already made the teacher-students and student-students more interactive. Furthermore, the students were even good in communicating and influencing their attitude so they participated actively in classroom activities and felt comfort interacting with the class using multilingual interaction. The researcher also suggests that future researchers should conduct the relevant research by adding some new aspects to it. The aspects can be extended in terms of the method used, the number of research variables, research participants, etc.